Retinal redetachment after pneumatic retinopexy – the importance of case selection - Muhammad Najmi K; Aida Zairani Mohd Zahidin; Mushawiahti Mustapha; Bastion MLC; Amin Ahem (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Pneumatic retinopexy is known as one of the treatment options for a specific type of retinal detachment. It is done in an office setting and may be the most cost-effective means of retinal reattachment surgery. Location and size of the retinal break remain as the major criteria for a successful outcome. We describe a case that fulfilled all except one major criteria for pneumatic retinopexy and underwent multiple procedures but failed. Fluctuation in the resolution of the retinal detachment such as in this particular case suggested possibility of early treatment failure.